Securing medical data transmission systems based on integrating algorithm of encryption and steganography - Hashim, Mohammed Mahdi; Taha, Mustafa Sabah; Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Mohd Rahim, Mohd Shafry; Islam, Shayla (Institute of Electrical and Electronics Engineers Inc., 2020)
The awareness to secure medical data has significantly increased. Steganographic has binged an important topic especially in this area since it has the capability to avoid medical data breach. This paper proposes a new steganography scheme based on Bit Invert System (BIS) using three control random parameters. The random selection process is performed based on Henon Map Function (HMF). In order to increase the security level, affine cipher and Huffman method is used for encryption as well as to minimize the encrypt data prior to the embedding for high payload ability. This integration is effective due to two main reasons: first, checking, and mapping to determine 0- and 1-bits during embedding, and second, segmenting the secret data to track and map every bit in stego image. The results showed that the presented scheme can assure confidentiality and security of the medical data while maintaining the image quality.